Effects of reinforcement on mechanical behaviour of cement treated sand using direct shear and triaxial tests. Issue 5 (3rd September 2018) - Malidarreh, N. R.; Shooshpasha, I.; Mirhosseini, S. M.; Dehestani, M.
Abstract : The mechanical behaviour of artificially cement-treated Babolsar sand reinforced with sack, polyethylene terephthalate (PET) and polypropylene (PP) fibres is studied in this paper. Tests were conducted on cemented sand samples prepared at a relative density of 70%, with and without reinforcements on direct shear and triaxial apparatuses. Effects of parameters such as fibre content (FC), fibre type and normal or confining pressure (NP or CP) have been studied. Test results revealed that the addition of fibres had a significant effect on the behaviour of cemented sand. However, PP fibres are much more effective reinforcing materials than sack and PET fibres. A comparison between the results of direct shear tests and triaxial tests indicated that the fibre efficiency and its effect on soil behaviour is much more significant in triaxial tests compared with those in direct shear tests.